Broccoli (Brassica oleraceae var. italica) growth performance in lowland using fertigation under protected rain shelter: the influence of spacings and accessions - Patricia Rachel Roney,; Lai, Lee San; Nur Najwa Hamsein,; Rahimah Sallehudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Broccoli (Brassica oleraceae var. italica) is traditionally grown in the highlands using an open system with 60 cm × 60 cm spacing. However, insect pests and disease infestation are limiting factors that cause major produce damage. Efforts have been made to increase the supply by cultivating them in protected rain shelters in lowlands to meet consumers' high demand. Consequently, the initial construction costs of infrastructures are substantial. Optimizing the rain shelter's space to increase yield and cover production costs is necessary. The performance of Broccoli accessions grown at various spacings in a closed rain shelter fertigation system in the lowland was evaluated. The treatments consisted of two plant spacings: S1- 30 cm × 30 cm and S2 - 60 cm × 60 cm, with five hot summer hybrid broccoli accessions: V1-accession BC114 (Chef 1856), V2-accession BC120 (Green Jade 2034), V3-accession BC123 (Royal Green), V4-accession BC124 (Green Magic), and V5-accession BC126 (V-075). Treatments were arranged in a Split Plot Randomized Design with three replications. Data on each spacing, accession & interaction’s vegetative growth, and yield performance were collected. The findings indicated that different spacing treatments did not significantly affect plant height, number of leaves, leaf length, leaf width, curd height, curd diameter, curd weight, or curd compactness. In comparison, when compared to other accessions, V4 and V5 generated noticeably greater curd yield, curd size, and growth. Only V5 significantly interacts with spacing treatments on days to curd initiation and days to curd maturity. The spacing treatment did not affect the yield of the accession V5. Very low (1%) pest incidence and no known disease infestation recorded. The findings suggest that the V4 and V5 accessions can be commercialized with 30 cm × 30 cm plant spacing to achieve optimal production yield in protected rain shelters in lowlands.